Water Rights Ownership In Sultanate Of Oman: A Case Study On The Aflāj Institution In Northern Oman - Al-marshoudi, Ahmed Salim Khalfan Ali (2024)
Using the ancient aflāj (singular falāj) system in Sultanate of Oman as a case study, this thesis investigates the Islamic water rights ownership and institution. This was conducted by analyzing the relationship of the physical water extraction variation among the three aflāj types in Oman and the development of water right types and the Islamic equitable principles/institutions. In literature many principles concerning water management and administration have been discussed. The most used one, in most Islamic studies, is how to manage water (as a natural gift) in relation with what Allah almighty given natural resource (also known as ecosystem) and human interaction. However, the focus of this thesis to fulfil the gap in our knowledge in how to provide a legal recognition of water rights ownership and institution. In fact, a guiding tool using Oakerson operational rule/institution which is considered as soft constrain for two main reasons: 1) decision making made operative only through human knowledge, choice, and action 2) rules found in decision making exist entirely in ream language (whether written or unwritten). It is these written and unwritten rules that have been applied in describing aflāj historical institutional (which researcher called Islamic equitable principles) and confirms with revealed information found within aflāj communities in Oman. In addition, Islamic equitable principles have been used to avoid confusion with another Islamic term known as uşūl al-fiĝh or jurisprudences.